Crude cellulase cocktail for lignocellulosic materials degradation - Abdul Aziz, Suraini; Hassan, Mohd Ali; Ismail, Mohd. Sukri; Sarbini, Razali; Ibrahim, Mohamad Faizal; Abdul Razak, Mohamad Nafis; Abu Bakar, Nurul Kartini; Phang, Lai Yee (2011)
The invention provides enzymes which are useful for degradation of lignocellulosic materials, which is obtained from Trichoderma asperellum UPM1 and Aspergillus fumigatus UPM2 and wherein the steps includes: (a) growing of the Trichoderma asperellum UPM1 and Aspergillus fumigatus UPM2; (b) carrying out fermentation process using the fungi grown from step (a) with substrates which has been treated to obtain enzymes; and (c) recovering the enzymes from fermented products obtained from step (b). The enzymes recovered include cellulases, xylaneses, pectinases or a combination of these enzymes which can be further used to hydrolyze lignocellulosic materials for fermentable sugars.